Incidence of household transmission of acute gastroenteritis (AGE) in a primary care sentinel network (1992-2017): cross-sectional and retrospective cohort study protocol - De Lusignan, S; Konstantara, E; Joy, M; Sherlock, J; Hoang, U; Coyle, R; Ferreira, F; Jones, S; O'Brien, S (BMJ Publishing Group, 2018)
INTRODUCTION: Acute gastroenteritis (AGE) is a highly transmissible condition. Determining characteristics of household transmission will facilitate development of prevention strategies and reduce the burden of this disease.We are carrying out this study to describe household transmission of medically attended AGE, and explore whether there is an increased incidence in households with young children. METHODS AND ANALYSIS: This study used the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) primary care sentinel network, comprising data from 1 750 167 registered patients (August 2017 database). We conducted a novel analysis using a 'household key', to identify patients within the same household (n=811 027, mean 2.16 people). A 25-year repeated cross-sectional study will explore the incidence of medically attended AGE overall and then a 5-year retrospective cohort study will describe household transmission of AGE. The cross-sectional study will include clinical data for a 25-year period-1 January 1992 until the 31 December 2017. We will describe the incidence of AGE by age-band and gender, and trends in incidence. The 5-year study will use Poisson and quasi-Poisson regression to identify characteristics of individuals and households to predict medically attended AGE transmitted in the household. This will include whether the household contained a child under 5 years and the age category of the first index case (whether adult or child under 5 years). If there is overdispersion and zero-inflation we will compare results with negative binomial to handle these issues. ETHICS AND DISSEMINATION: All RCGP RSC data are pseudonymised at the point of data extraction. No personally identifiable data are required for this investigation. The protocol follows STrengthening the Reporting of OBservational studies in Epidemiology guidelines (STROBE). The study results will be published in a peer-review journal, the dataset will be available to other researchers.